Poisoning effects of H2S and HCl on the naphthalene steam reforming and water-gas shift activities of Ni and Fe catalysts - Dou, Xiaomin (2019)
H2S and HCl are common impurities in raw syngas produced during gasification of biomass and municipal solid waste. The purpose of this study was to investigate the poisoning effect of H2S and HCl on synthesized and commercial catalysts during steam reforming of naphthalene. Four synthesized catalysts with different loadings of Ni and Fe on alumina support and two commercial catalysts were selected and evaluated in a fixed bed reactor at 790, 850 and 900 °C. The obtained results revealed that reforming and water-gas shift (WGS) activities of catalysts did not benefit from the Fe addition. The activities were influenced differently by H2S and HCl indicating that the reactions were catalyzed by different active sites on the nickel surface. In the presence of H2S and HCl, the poisoning of naphthalene reforming activity was caused by H2S and was not affected by HCl when both compounds were present in the gas. H2S chemisorbs on nickel surface forming NiS and decreasing the accessibility of active sites to hydrocarbons. The poisoning effect was only partially reversible. On the contrary, the poisoning of WGS activity could be caused by both H2S and HCl, and the activity could be completely restored when H2S and HCl were removed from the gas. Unlike naphthalene reforming activity, which was comparable for catalysts with similar Ni loadings, WGS activity depended on the catalyst structure and was less susceptible to poisoning by H2S and HCl in case of the catalyst with strong NiO-support interactions.